Next Wave in Robotics 14th FIRA RoboWorld Congress, FIRA 2011, Kaohsiung, Taiwan, August 26-30, 2011. Proceedings - Li, Tzuu-Hseng S.; Tu, Kuo-Yang.; Tsai, Ching-Chih.; Hsu, Chen-Chien.; Tseng, Chien-Cheng.; Vadakkepat, Prahlad; Baltes, Jacky; Anderson, John.; Wong, Ching-Chang.; Jesse, Norbert; Kuo, Chung-Hsien.; Yang, Haw-Ching.; et al. (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 14th RoboWorld Cup and Congress of the Federation of International Robosoccer Association, FIRA 2011, held in Kaohsiung, Taiwan in August 2011. The 34 revised papers presented were carefully reviewed and selected for inclusion in the proceedings out of a total of 110 contributed papers presented at FIRA 2011. The papers address a broad variety of current topics in robotics research, particularly in robot soccer.
Keywords: Computer science; Artificial intelligence; Computer vision; Computer Science; Artificial Intelligence (incl. Robotics).; Image Processing and Computer Vision; Robotics and Automation